A population-based study of interactions between high-risk human papillomavirus infection and vaginal local cytokines CD4 CD8 IL-10 with cervical intraepithelial neoplasia - Zhu, Ruoxi; Yang, Aimin; Wang, Wenhao; Zhao, Weihong; Wang, Wei; Wang, Zhilian; Wang, Jintao; Hou, Yongli; Su, Xiaoqiang; Zhang, Lili; Feng, Bo; Yang, Jing; et al. (Frontiers in Oncology, 2025)
BackgroundCluster of Differentiation-4(CD4),Cluster of Differentiation-8(CD8), and interleukin-10 (IL-10) have long been considered to be related to cervical cancer, but the exact relationship remains unclear. Few studies investigated the relationship between CD4,CD8,IL-10, and high-risk human papillomavirus (HPV) with risk of cervical intraepithelial neoplasia (CIN).ObjectiveOur aim is to evaluate the relationship between CD4, CD8, IL-10, and high-risk HPV infection with the risk of CIN, as well as their interactions on CIN.DesignIn 2014-2015, a cross-sectional study of screening data was conducted among 2285 women aged 19–65 years who participated in an ongoing community-based cohort of 40,000 women in Shanxi, China. Using categorical and spline analyses to evaluate the relationship between local vaginal fluids of CD4,CD8,CD4/CD8,IL-10, and CIN risk. A total of 1,503 controls were followed up until January 31, 2019. A nested case-control study was used to assess the relationship between vaginal lavage CD4, CD8, CD4/CD8, and IL-10 levels and the risk of CIN progression.ResultsAfter adjusting for possible confounding factors,CD4 and CD8 levels were positively related to CIN risk (the 1st versus 4th quartile CD4,CD8 OR = 0.45[0.34, 0.60] and 0.34[0.26, 0.45] for CIN1, 0.32 [0.21, 0.48] and 0.24 [0.16, 0.38] for CIN2/3). Increased CD4 and CD8 levels were positively related to the occurrence of CIN(P-overall<0.01).CD4/CD8 levels and the risk of CIN1 followed a nonlinear “U-shape” (P-nonlinear <0.01). IL-10 levels and the risk of CIN1 followed a nonlinear “n-shape”(P-nonlinear <0.01).IL-10 levels were inversely related to the occurrence of CIN2/3(OR = 3.87, [2.49, 6.00],P-overall<0.01). The highest risk of CIN was observed in women with high-risk HPV, whose CD4 and CD8 levels were the highest(P-interaction < 0.01).Patients with the lowest IL-10 levels(IL-10 ≤ 53.17pg/ml) who are positive for high-risk HPV infection have the highest risk of CIN2/3(OR = 18.46,[9.33-36.51]). Nested case-control analysis observed a positive relationship between CD4,CD8 levels, and risk of CIN progression (CD4 OR = 0.34,[0.13, 0.94];CD8 OR = 0.27, [0.09, 0.79]),and an opposite relationship between IL-10 levels and risk of CIN progression (OR = 2.92, [1.09, 7.84]).ConclusionsLocal vaginal CD4 and CD8 levels were positively correlated with CIN risk, and IL-10 levels were inversely correlated with CIN2/3, whether or not with high-risk HPV infection in Chinese women.